Basal cell carcinoma margin delineation: is curettage useful? A surgical and histological study. (June 2013) - Dika, Emi; Fanti, Pier Alessandro; Ismaili, Alma; Misciali, Cosimo; Vaccari, Sabina; Barisani, Alessia; Patrizi, Annalisa
<x xml:space="preserve">Abstract</x> Basal cell carcinoma (BCC) is the most common variety of non-melanoma skin cancer. Treatment modalities include cryotherapy, topical imiquimod 5% cream, photodynamic therapy, electrodessication and curettage, classic surgical excision, Mohs surgery, and radiotherapy. Surgical treatments are regarded as the most effective, but, in some cases, may produce poor cosmetic outcomes. Delineating tumor margins as much as possible is important in order to limit broad surgical excisions. Preoperative curettage is a surgical technique proposed to delineate BCC margins. Reported data on curettage utility are controversial. Some authors report that curettage better delineates the tumor, decreasing relapsing rates, whereas others consider it as a nonspecific procedure that may damage the surrounding healthy tissue and falsely increase the final defect size. We studied the pathologic features of curetted material and the main surgical specimens of 55 BCC treated with preoperative curettage. According to BCC subtype, preoperative curettage may lead to a complete or almost complete tumor removal. Preoperative curettage might be helpful in delineating BCC margins, especially in nodular and superficial BCC. No evidence of unspecific removal of tumor's surrounding healthy tissue was observed in our specimens.